WOMEN EMPOWERING THROUGH DECOUPAGE - Hommy Dorthy Ellyany Sinaga; Petrus Loo; Dedy Lazuardi; Sri Rezeki; Norhaslina BT Asri; Mashitah Binti Duralim; Nur Fadzillah Binti Jaafar (Smart Education, 2024)
Abstract: The community service activity